'I couldn't even talk to the patient': barriers to communicating with cancer patients as perceived by nursing students - Lin, M.; Hsu, W.; Hung, M.; Su, Y.; Crawford, Paul; Tang, C. (Wiley, 2017)
Communication is closely related to safe practice and patient outcomes. Given that most clinicians fall into routines when communicating with patients, it is important to address communication issues early. This study explores Taiwanese nursing students’ experiences of communication with patients with cancer and their families. Senior nursing students who had cared for cancer patients were recruited to participate in focus group interviews. These semi-structured interviews were recorded and transcribed for content analysis. Among the 45 participants, about 36% of them never received any communication training. Up to 76% of the participants stated that their communication with cancer patients was difficult and caused them emotional stress. Subsequent data analysis revealed four themes: dis-engagement, reluctance, regression, and transition. Students’ negative communication experiences were related to the patients’ terminally ill situation; the students’ lack of training, low self-efficacy and power status, poor emotional regulation, and cultural considerations. The findings of this study provide a deeper understanding of nursing students’ communication experiences in oncology settings within the cultural context. Early and appropriate communication training are necessary to help students regulate their emotions and establish effective communication skills. Further studies are needed to examine the relationship among students’ emotional labor, communication skills and outcomes.